Bioefficacy of Different Bioagents Against Fusarium Oxysporum F. SP. Carthami (Journal of Plant Disease Sciences, 2023)
Significant Oilseed Crop Farmed in Over 60 Countries Worldwide (Gilbert, 2008). With an Acreage of 5.17 Lakh Hectares, India Is the World’s Second Largest Producer of Safflower (43.67 MT), Yet Its Average Yield Is Only 843 KG/Ha (Anonymous, 2020). Fusariumoxysporum F. SP. Carthami Is a Pathogen Found in Soil and Seeds That Causes Safflower Wilt. Fusarium Wilt Has Become the Key Limiting Issue for Safflower Production in India (Sastry and Chattopadhyay, 2003), Causing the Country to Lose Its Status as the World’ S Leading Producer of Safflower.chemical Fungicides, Despite Their Severe Environmental Implications, Are Currently Farmers’ Preferred Choice for Disease Control Due to Their Ease of Usage and Rapid Recovery. When Seed Treatment With Fungicides Fails to Protect Crops for an Extended Period of Time, Alternative Control Strategies, Such as Biological Control, Are Claimed to Be an Effective, Safe, and Environmentally Friendly Approach to Plant Disease Management.considering the Benefits of Bio- Agents, the Current Study Was Conducted to Evaluate the Efficacy of Different Bioagents Against Fusarium Oxysporum F. SP. Carthami in Safflower Under in Vitro conditions.
Keywords: BIOEFFICACY; DIFFERENT; FUSARIUM